Turbulent asymptotic suction boundary layers studied by simulation - Schlatter, Philipp; Orlu, Ramis (Journal of Physics: Conference Series, 2011)
The turbulent asymptotic suction boundary layer (ASBL) is studied using numerical simulations. Uniform suction is applied on the wall in order to compensate for the momentum loss inflicted by the wall friction. Four Reynolds numbers, defined as the ratio of free-stream velocity and suction rate, Re = 333, 400 and 500, are considered, whereas Re = 280 relaminarised. In agreement with previous studies, suction causes the fluctuation intensities to decrease, and the near-wall anisotropy to increase. The shape of the mean velocity profile is considerably changed yielding a decreased slope in the overlap region. It is shown that even for moderate suction rates large values for the friction Reynolds number Reτ = δ99+ are obtained; at Re = 333 a value of Reτ = 1900 is reached and Re = 400 yields Reτ = 5700. Artificially using smaller computational domains, limiting the size of the largest turbulent structures, gives unexpected results: The mean velocity profile starts to show a distinct wake region which only disappears for large enough domains. Moreover, the boundary layer thickness δ99 strongly depends on the chosen domain size. Spectral maps of the flow are analysed, showing an outer peak appearing at a spanwise size of about 0.6δ99, albeit with considerably lower amplitude compared to cases without suction. Visualisations of the flow are also discussed.
CRIS-Team Scopus Importer:2023-03-21